2014
DOI: 10.1002/wsb.414
|View full text |Cite
|
Sign up to set email alerts
|

A test of the Swainson's warbler habitat suitability index model

Abstract: We tested a recent Habitat Suitability Index (HSI) model proposed for the Swainson's warbler (Limnothlypus swainsonii; a species of conservation concern in the southeastern United States) using data on habitat, bird occupancy, and abundance collected at White River National Wildlife Refuge, Saint Francis National Forest, and Big Island in Arkansas between 2005 and 2010. The Swainson's warbler HSI includes a combination of 6 variables: landform, landcover, successional age class, forest patch size, proportion f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 24 publications
0
22
0
Order By: Relevance
“…Normalized density was a statistically-significant exponential function of HSI, providing validity of the HSI as a robust predictor of suitable habitat for oyster sanctuary restoration in Pamlico Sound. Positive relationships between indices of abundance and HSI have been identified previously in validation studies, but the relationships have generally been linear or sigmoidal (Cho et al, 2012;Reiley et al, 2014;Theuerkauf and Lipcius, 2016). The exponential relationship between HSI and normalized density can be used, through inverse calculations, to determine HSI values needed to reach restoration targets (i.e., target normalized density of 2,000 generally occurs at HSI values > 0.45).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Normalized density was a statistically-significant exponential function of HSI, providing validity of the HSI as a robust predictor of suitable habitat for oyster sanctuary restoration in Pamlico Sound. Positive relationships between indices of abundance and HSI have been identified previously in validation studies, but the relationships have generally been linear or sigmoidal (Cho et al, 2012;Reiley et al, 2014;Theuerkauf and Lipcius, 2016). The exponential relationship between HSI and normalized density can be used, through inverse calculations, to determine HSI values needed to reach restoration targets (i.e., target normalized density of 2,000 generally occurs at HSI values > 0.45).…”
Section: Discussionmentioning
confidence: 93%
“…To determine the form of the relationship between HSI and normalized oyster density, we used a global curve fitting program (Systat, 2007) to fit linear, exponential, quadratic and sigmoid functions to the relationships based on functions selected in previous HSI studies (Soniat and Brody, 1988;Reiley et al, 2014;Theuerkauf and Lipcius, 2016). Akaike Information Criterion (second-order bias correction estimator, AICc) was used to verify the best fitting model of the four possible functions.…”
Section: Model Validationmentioning
confidence: 99%
“…Recent HSI validation studies have indicated that unvalidated HSIs can be unreliable indicators of habitat quality (Reiley et al, 2014). Although widely used, HSI models have been criticized as unreliable and lacking scientific rigor (Cole and Smith, 1983;Roloff and Kernohan, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Although widely used, HSI models have been criticized as unreliable and lacking scientific rigor (Cole and Smith, 1983;Roloff and Kernohan, 1999). Despite the potential cost associated with obtaining these independent datasets, the validation process is required to determine the reliability and utility of these models if they are to inform species conservation and management (Brooks, 1997;Tirpak et al, 2009;Reiley et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation